A formação na escola pelo Programa Pacto - Duarte, Volmar (2018)
For more than fifteen years of experience in education, we have observed, among other reasons, students' lack of motivation for studies, high rates of school dropout, and a considerable number of class council approvals as a form of deceiving the disapproval rate, which would be quite high. These factors have considerably difficult the achievement of expectations, which we hope to achieve in the teaching-learning process with the students. Facing this framework, with the development of this research, anchored in a case study, we present the attributions, perspectives and limits of a Continuing Teacher Training Program, according to procedures proposed by the Ministry of Education (MEC): National Pact for Secondary Education Strengthening. The purpose of the research is the following question: “How did the National Pact for the Secondary Education Strengthening contribute to changes in teachers' pedagogical work?” The research locus was Padre Anchieta State School from Salgado Filho PR (CEPA), a school institution that faces an educational reality not different from the other Brazilian schools, regarding the teaching and learning process. One of the main purpose of the Pact consists on the integral formation of the students of the High School, providing them conditions and possibilities of knowledge construction for autonomy and citizenship. Therefore, the results of the present research aim to analyze the objectives of the National Pact for the Secondary Education Strengthening in the view of high school teachers, pedagogues, principal and teachers of Higher Education Institutions to verify the results, through the implantation of this training, in this school institution. The methodology of the present research was based, mainly, on the case study carried out by Yin (2010), for the relevance that it presents regarding to the ways of analyzing a certain educational policy, in this case, teacher training and the possible results at pedagogical work. Besides the analysis of the work of 10 (ten) books used during the formation of the teachers by the Pact, we use Bernard Charlot, Marilena Chauí, Marai Ciavatta, Antonio Gramsci, Francisco Imbernon, among others, as basis for academic grouding. On this basis, we evaluated the results of this Teacher Training Program working with 17 high school teachers, who participated in the National Pact for the Secondary Education Strengthening, with 4 (four) members of the pedagogical team: three (3) pedagogues, the principal and three (3) teachers of Higher Education Institutions (IES) who participated in the execution of the Teacher Training Program.